Integration analysis based on fatty acid metabolism robustly predicts prognosis, dissecting immunity microenvironment and aiding immunotherapy for soft tissue sarcoma - Liu, Binfeng; He, Shasha; Li, Chenbei; Feng, Chengyao; Wang, Hua; Zhang, Haixia; Tu, Chao; Li, Zhihong (Frontiers in Genetics, 2023)
Abstract Background: Soft tissue sarcoma (STS) is a highly malignant tumor with a dismal prognosis. Presently, the dysregulation of fatty acid metabolism has received more and more attention in tumor research, but fewer reports are relevant to STS. Methods: Based on fatty acid metabolism-related genes (FRGs), a novel risk score for STS was developed utilizing univariate analysis and Least Absolute Shrinkage Selection Operator (LASSO) Cox regression analyses in the STS cohort, which were further validated using the external validation cohort from other databases. Furthermore, the independent prognostic analysis, C-index, ROC curves, and nomogram were carried out to investigate the predictive performance of fatty acid-related risk scores. We also analyzed the differences in enrichment pathways, immunity microenvironment, gene mutations, and immunotherapy response between the two distinct fatty acid score groups. Moreover, the Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) was further verified the expression of FRGs in STS. Results: A total of 153 FRGs were retrieved in our study. Next, a novel fatty acid metabolism-related risk score (FAS) was constructed based on 18 FRGs. The predictive performance of FAS was also verified in external cohorts. In addition, the independent analysis, C-index, ROC curve, and nomograph also revealed that FAS could serve as an independent prognostic factor for the prognosis prediction of STS patients. Meanwhile, our result demonstrated that the STS cohort in two distinct FAS groups had different copy number variations, immune cell infiltration, and immunotherapy response. Finally, the in vitro validation results demonstrated that several FRG included in the FAS exhibited an abnormal expression in STS. Conclusion: Altogether, our work comprehensively and systematically clarifies fatty acid metabolism's potential roles and clinical significance in STS. The novel individualized score based on fatty acid metabolism may be provided as a potential marker and treatment strategy in STS.